Senescent profile of angiogenic T cells from systemic lupus erythematosus patients. Issue 3 (31st July 2015) - López, Patricia; Rodríguez-Carrio, Javier; Martínez-Zapico, Aleida; Caminal-Montero, Luis; Suarez, Ana
Abstract : CD28 null-T cells in SLE patients is associated with inflammatory, rather than protective, effects. Abstract: The chronic inflammatory environment associated with systemic lupus erythematosus can lead to an accelerated immunosenescence responsible for the endothelial damage and increased cardiovascular risk observed in these patients. The present study analyzed two populations with opposite effects on vascular endothelium, angiogenic T cells and the senescent CD4 + CD28 null subset, in 84 systemic lupus erythematosus patients and 46 healthy controls. Also, 48 rheumatoid arthritis patients and 72 individuals with traditional cardiovascular risk factors participated as disease controls. Phenotypic characterization of CD28 + and CD28 null cells was performed by analyzing markers of senescence (CCR7, CD27, CD57) and cytotoxicity (CD56, perforin, granzyme B, IFN-γ). IL-1β, IL-6, IL-8, IL-10, IL-12, IL-17A, IFN-α, IFN-γ, TNF-α, B lymphocyte stimulator, and GM-CSF serum levels were analyzed in systemic lupus erythematosus patients and healthy controls. CD4 + CD28 null cells were notably increased in the systemic lupus erythematosus patients and disease controls compared with healthy controls. In contrast, angiogenic T cells were only reduced in the disease controls (those with rheumatoid arthritis or traditional cardiovascular risk factors). Nevertheless, an anomalous presence of CD28 null -angiogenic T cells, with cytotoxic and senescent characteristics, was noted in systemic lupus erythematosus patients in association with anti-dsDNA titer, anti-SSA/Ro antibodies and circulating TNF-α, IL-8, IFN-α, and B lymphocyte stimulator amounts. This subset was also detected in those with traditional cardiovascular risk factors but not in the rheumatoid arthritis patients. In contrast, CD28 + -angiogenic T cells were reduced in the systemic lupus erythematosus patients with cardiovascular disorders. In conclusion, CD28 expression must be used to redefine the angiogenic T cell population, because in pathologic conditions, a senescent CD28 null -angiogenic T cell subset with inflammatory, rather than protective, effects could be present.